THE WOMAN’S POSITION IN THREE ONLINE NEWS OF CHILDREN SEXUAL HARASSMENT IN LUWU TIMUR - Pangestu, Maulani; Buansari, Istihayyu (Universitas Gunadarma, 2023)
The objective of this study is to investigate and to find a crystal-clear picture of a woman’s position in three online news which discussed children’s sexual harassment in Luwu Timur, Indonesia. This is a qualitative study which use critical discourse analysis techniques. The objects of study are three online news which distributed by www.liputan6.com, www.nasional.okezone.com, and www.pikiran-rakyat.com. All online news was written by three different reporters and was released after the case is closed by Indonesian Police. All the source data were analysed by using the Sara Mills model i.e., the subject-object position and the writer-reader. There are found that two from three online news texts were pictured women as the subject rather than object while two online news texts considered the reader important while the remaining excluded the position of readers. The benefits of this study – it could be used as additional information and reference for anyone who wants to study critical discourse analyses especially Sara Mills model.